2022
DOI: 10.1111/jam.15389
|View full text |Cite
|
Sign up to set email alerts
|

Application of pulsed light technology for fruits and vegetables disinfection: A review

Abstract: Non-thermal technologies can maintain fruit and vegetable products quality better than traditional thermal processing. Pulsed light (PL) is a non-thermal method for microbial inactivation (vegetative cells and spores) in fruits and vegetables. The PL treatment involves the application of intense and short-duration pulses of broad spectrum wavelengths ranging from UV to near-infrared (100-1100 nm). This review summarized application of PL technology to control microbial contamination and increasing shelf-life o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
4
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 19 publications
(5 citation statements)
references
References 69 publications
0
4
0
1
Order By: Relevance
“…Hee-Jeong Hwang and colleagues found that the bactericidal effect of IPL varies considerably even in different liquid samples, such as in mineral water, carbonated drinks, and coffee, because of the differences in absorption properties and light transparency ( Hwang et al, 2015 ). The most important factor in determining the effectiveness of IPL inactivation is the beam incident on the sample, in addition to factors, such as product area, thickness, transparency, color, viscosity, presence of particulate matter, type of microorganism, and absorption characteristics of the food ( Salehi, 2022 ). One of the shortcomings of this study is that it does not show the bactericidal effect of IPL on bacteria on food, data on which we will subsequently publish in a separate paper.…”
Section: Discussionmentioning
confidence: 99%
“…Hee-Jeong Hwang and colleagues found that the bactericidal effect of IPL varies considerably even in different liquid samples, such as in mineral water, carbonated drinks, and coffee, because of the differences in absorption properties and light transparency ( Hwang et al, 2015 ). The most important factor in determining the effectiveness of IPL inactivation is the beam incident on the sample, in addition to factors, such as product area, thickness, transparency, color, viscosity, presence of particulate matter, type of microorganism, and absorption characteristics of the food ( Salehi, 2022 ). One of the shortcomings of this study is that it does not show the bactericidal effect of IPL on bacteria on food, data on which we will subsequently publish in a separate paper.…”
Section: Discussionmentioning
confidence: 99%
“…In the case of acerolas (a brazilian berry), blueberries, strawberries and tomatoes, the optimal dose of PL, to control microorganism infection or to extend the shelf life, were identified as 0.6, 1.27, 1.27 and 2.2 J cm −2 , respectively (Macedo et al, 2023; Salehi, 2022). These berries and tomato, possess a thinner epicarp along with a softer physical barrier, which their optimal PL doses are lower than of melons.…”
Section: Discussionmentioning
confidence: 99%
“…PL is notably effective in killing foodborne pathogens on food surfaces without incurring detrimental effects on the food itself or invoking the use of potentially noxious or contaminating chemicals. For instance, the treatment of blueberries and strawberries with PL resulted in a 0.9 and 4.3 log CFU/g reduction in Salmonella , while preserving the nutritional composition of the blueberries (Cao et al., 2017; Salehi, 2022). Another investigative study showcased that PL treatment effectively inactivated Salmonella on the surface of lettuce, accomplishing a reduction of 5.40 log CFU/g (Tao et al., 2019).…”
Section: Methods For Fruits and Vegetables Safety Protectionmentioning
confidence: 99%